กระบวนการตกเป็นเหยื่อการค้ามนุษย์ของลูกเรือประมงไทย : ศึกษากรณีเหยื่ออาชญากรรมในสถานคุ้มครองและพัฒนาอาชีพ (ชาย) จังหวัดปทุมธานี - ทานตะวัน แก้วสม (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To study ideas about the victimization of seamen through human trafficking; factors contributing to the human trafficking of seamen; and measures to prevent and resolve human trafficking in seamen. Information and data were taken from articles and other printed sources of information regarding human trafficking. Other research methods used were qualitative research and indepth interview techniques. Population samples used are the victimized seamen, professionals and experts on the issue about human trafficking, and owners of sea fishing business. The results showed that the seamen usually victimized by human trafficking are males aged 17 to 42 years old. Most are of working age, and who are physically strong and robust. These men are usually "picked" out in public places such as Sanam Luang Park, Hua Lampong train station, and in public parks in and nearby Bangkok. A stranger usually befriends the identified victim. As the friendship develops, he will then persuade the victim about a job usually with the enticement of big salaries. Factors that contribute to the human trafficking of seamen include personal factors, economic factors, social factors and environmental factors. Education, family background, needs, personality and behavior are examples of personal factors. Economic factors at the micro-level such as community economic structure, occupation, money income and at the macro-level such as the economic development of the country are also to be considered. Moreover, social factors such as values and migration trends also have their effects. Environmental factors that may be considered include location-risk, residential areas and neighborhoods. One way to combat trafficking is through active campaign and information dissemination so that people have a better understanding about human trafficking and thus protect them from the trafficking cycle. Government, civil society, the private sector, educational and religious sectors, and all sectors of society must cooperate and work together to seriously solve the problem of human trafficking. Owners of businesses using labor force must be humane and must have an awareness to help and be vigilant against human trafficking in their areas. Human trafficking problem will at least be reduced if not eliminated.